Interictal Single-Voxel Proton Magnetic Resonance Spectroscopy of the Temporal Lobe in Dogs With Idiopathic Epilepsy - Olszewska, Agnieszka; Schmidt, Martin Jürgen; Failing, Klaus; Nicpoń, Józef; Podgórski, Przemysław; Wrzosek, Marcin Adam (Frontiers in Veterinary Science, 2020)
Proton magnetic resonance spectroscopy (H1-MRS) could provide insight into the metabolic pathophysiology of the temporal lobe of canine brain after seizure. Currently, there is no evidence-based data available on MRS of temporal lobe in dogs with idiopathic epilepsy (IE). The aim of this prospective, cross-sectional study was to evaluate the interictal metabolic activity of the temporal lobe in IE dogs compared to a control group with the use of H1-MRS. Ten healthy dogs and 27 client-owned dogs with IE underwent 1.5-Tesla magnetic resonance imaging (MRI) and single-voxel H1-MRS. The MRS studies were acquired as spin echoes with a repetition time (TR) of 2,000 ms and an echo time (TE) of 144 ms. A cubic voxel (10 ×10 ×10 mm) was positioned bilaterally into the region of the left and right temporal lobe, including a middle part of the hippocampus and the amygdala. The N-acetylaspartate (NAA)-to-creatine (NAA/Cr), NAA-to-choline (NAA/Cho), choline-to-creatine (Cho/Cr), and choline-to-NAA (Cho/NAA) ratios were determined in both hemispheres and compared to controls. No significant differences in all metabolite ratios between epileptic dogs and the control group could be found. A time-dependent decrease in the NAA/Cho ratio as well as an increase in the Cho/NAA ratio was found with proximity in time to the last seizure. We found no correlation between metabolite ratios and age or sex in this animal group. Time span from the last seizure to the acquisition of MRS significantly correlated with NAA/Cho and Cho/NAA ratio. We conclude that without a time relation, metabolite ratios in dogs with IE do not differ from those of the control group.